Seven Years of Implementing UNESCO's 2003 Intangible Heritage Convention—Honeymoon Period or the "Seven-Year Itch"?. Issue 3 (17th December 2014) - Blake, Janet
Abstract: This article aims to examine how far our experience of implementing UNESCO's Intangible Heritage Convention, which was adopted in 2003 and entered into force in April 2006, over the last seven years has transformed our understanding of intangible cultural heritage and of its safeguarding. There have been, of course, both positive and negative impacts thus far as well as both unexpected and, thus far, unknown outcomes. The Convention broke new ground, introducing new terminology and new definitions of existing terms and requiring a reexamination of some approaches to international and national law making and policymaking. When considering the impact of the 2003 Convention internationally, we need to look, inter alia, at its impact on international policymaking (including cultural policy, the sustainable development agenda and indigenous rights), related developments in other areas of international law (including human rights and environmental law), and the way in which states treat shared heritage that crosses international frontiers. On the national level, we should consider how the Convention may have contributed to creating a new paradigm for identifying and safeguarding intangible cultural heritage (ICH), shifting the focus of significance, redefining the role of non-state actors vis-à-vis state authorities in this process and, even, moving the idea of national heritage away from a purely state-driven concept. Important questions to consider include whether the Convention has resulted in the development of new national policy strategies for (a) promoting the function of ICH in society and (b) integrating ICH into planning and development programs and how effectively Parties have managed to engage communities, groups, and individuals in the aforementioned activities.